APPLICATION OF INFRARED RADIATION ON DRYING CHARACTERISTICS OF EGGPLANT SLICES - Doymaz, I. (PLAPIQUI(UNS-CONICET), 2017)
The effect of infrared power on drying kinetics of eggplant slices was investigated. The eggplant slices were dried at 83, 125 and 167 W infrared power levels and for slice thicknesses of 0.6, 0.9, and 1.2 cm. It was observed that drying and rehydration characteristics of eggplant slices were greatly influenced by pre-treatment, slice thickness and power level. Literature drying models of Lewis, Henderson and Pabis, Midilli et al., Page and Weibull as well as a logarithmic rate were fitted to experimental data using nonlinear regression analysis. Midilli et al. model has shown a better fit to experimental drying data as compared to other models. Effective moisture diffusivity ranged from 0.28x10(-9) to 1.09x10(-9) m(2)/s calculated using the Fick's second law.
Keywords: Effective moisture diffusivity; eggplant slices; infrared drying; mathematical modeling; PRETREATMENTS; KINETICS; QUALITY; FRESH; L.; Engineering